Regular Exposure to Cowbells Affects the Behavioral Reactivity to a Noise Stimulus in Dairy Cows - Johns, Julia; Masneuf, Sophie; Patt, Antonia; Hillmann, Edna (Frontiers in Veterinary Science, 2017)
In alpine regions, cows are often equipped with bells during pasture season to ensure that farmers can locate them. Constant exposure to the chime of a bell may affect cows’ acoustic perception in general. The aim of the present study was to test if routine bell exposure affects the reactivity to a noise stimulus and might be associated with hearing impairment in cows. For the assessment, behavioral and cardiac indicators were used as indirect measures of hear-ing capacity. Cows that were either used to wearing a bell or not were exposed to a playback of low and high amplitude (= varying loudness). Additionally, we tested whether wearing earplugs, mimicking hearing impairment, reduced the cows’ reactivity towards the playback. On 24 farms, half of them routinely using cowbells, 96 Brown Swiss cows were tested in a 2×2 factorial cross-over design (65 or 85 dB, without or with earplugs) in a balanced order. The effect of bell experience, amplitude and earplugs on the latency to the first behavioral and cardiac response to a 5-second playback was analyzed using linear mixed effects models, con-sidering dependencies within the dataset. Cows reacted faster without earplugs and when they were exposed to 85 dB compared with 65 dB. The proportion of cows leaving the feed-ing rack after onset of the playback was reduced by bell experience and earplugs, and was increased when exposed to 85 dB compared with 65 dB. Exposure without earplugs to 85 dB but not to 65 dB increased heart rate. Heart rate as well as heart rate variability indicated in-creased sympathetic activation during the exposure to 85 dB compared with 65 dB. In gen-eral, behavioral and cardiac indicators did not indicate severe hearing impairment due to rou-tine bell exposure. The 85 dB stimulus increased arousal and avoidance compared with the 65 dB stimulus, with bell experience and earplugs leading to a general decrease in avoidance of the stimulus. This may reflect an altered acoustic perception of the playback stimulus in dairy cows that are routinely exposed to bells.